The Difference of Students’ Mathematical Communication Ability Taught by Cooperative Learning Model Think Talk Write Type and Numbered Head Together Type - Meiva Marthaulina Lestari Siahaan; E. Elvis Napitupulu (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2018)
The purpose of this research was to know there was any difference in student’s mathematical communication ability in cooperative learning Think TalkWrite (TTW) type and Numbered Head Together (NHT) type. The population was all students at SMP Negeri 1 Lubuk Pakam. The sample was two classes which each consist of 36 students, VII A as experimental class I which taught by TTW and VII B as experimental class II which taught by NHT. The sample was taken by cluster random sampling. Collecting data technique of this research was mathematical comunication ability essay test that was given in the end of learning either in experimental class I or experimental class II. From the data analysis of each of experimental class were obtained that the average of posttest score in TTW classroom was higher than in NHT classroom. It was also obtained that score of mathematical communication indicators in TTW classroom was higher than in NHT classroom. From the data analysis of posttest score by using t-test with significance level α = 0.05, it was obtained that tcount = 4.687 and ttable = 1.667. It means that tcount > ttable then H0 was rejected and Ha was accepted. So, it can be concluded that there was difference of student’s mathematical communication ability who taught by cooperative learning model type TTW with NHT at SMP Negeri 1 Lubuk Pakam.